VIBRATION ANALYSIS OF INDIAN HUMAN SUBJECT IN SITTING POSTURE - Singh, J.; Savara, S.; Kalsi, S.; Singh, I.; Sehgal, S.S.; Nigam, S.P. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
The human body shows a non-linear and dynamic behavior under different vibration conditions that occur while travelling, walking and performing other activities.Thus, it becomes necessary to study effects on the human body that lead to different types of body pain and discomfort. In this study, an attempt has been made to find out natural frequencies and mode shapes of an Indian male subject in sitting posture without backrest using FEM approach. The results will be helpful in the designing of products for human use like automobile seats and machine parts to minimize the effect of vibrations on human body. A 3-D CAD model of human subject was generated using physical dimensions and anthropometric data available in the existing literature. A CAD model of the human body was segmented into a simple model using segments of ellipsoidal shape. As observed from this study, at 2.8 Hz maximum deformation of 56 mm occurred at head segment and with the increase in natural frequency it started diverting to lower arms. At 18.7 Hz, maximum deformation (124 mm) occurred at lower arms of human subject.Also, no deformation occurred at lower body segments below hip joint.The results obtained are in validation with the existing literature.